2019
DOI: 10.1088/2515-7647/ab437b
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-optic based particle sensing via deep learning

Abstract: We demonstrate the capability for the identification of single particles, via a neural network, directly from the backscattered light collected by a 30-core optical fibre, when particles are illuminated using a single mode fibre-coupled laser light source. The neural network was shown to be able to determine the specific species of pollen with ∼97% accuracy, along with the distance between the end of the 30core sensing fibre and the particles, with an associated error of±6 μm. The ability to be able to classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The authors in [123] used CNN to demonstrate the capability for the identification of specific species of pollen from the backscattered light. Thirty-core optical fiber were used to collect the backscattered light.…”
Section: Cnn-based Applicationsmentioning
confidence: 99%
“…The authors in [123] used CNN to demonstrate the capability for the identification of specific species of pollen from the backscattered light. Thirty-core optical fiber were used to collect the backscattered light.…”
Section: Cnn-based Applicationsmentioning
confidence: 99%
“…Several researchers proposed various pattern recognition algorithms, such as Jiao et al, [108] who demonstrated a remote fiber coupled method for classifying particles via analysis of their backscattered light. The illumination source is a fiber-coupled laser diode and backscattered light is collected via a 30-core fiber.…”
Section: Anomaly Detection and Event Classification For Pointwise Fosmentioning
confidence: 99%
“…The deep learning model even predicted the distance the particle was from the end of the fiber through the intensity of scattered light. 7 Hollow core fibers were utilized as an unconventional optical cavity with a confined particle, for sensing fluctuations in the environment for quantities such as temperature or electric field. 8,9 In these instances, the incorporation of freely diffusing particles in the hollow cores has no interference on the monitoring and measurement process.…”
Section: Introduction: Optical Fiber Sensorsmentioning
confidence: 99%